Les hominoïdes fossiles : une aide pour l’éducation en Afrique - Brigitte Senut (Revue de Primatologie)
Africa is a key continent for unravelling hominid history shared with that of apes and to understand the emergence of our family in relation to the environment. Today numerous international field expeditions carry out researches on the continent and especially in East Africa. The rich fossil heritage discovered in often isolated places is transported to national museums (created mostly by expatriates during colonial period) and located in the capitals where access is easy for international researchers but difficult for the people who are living close to the fossil sites. What happens at the local level? Generally, the local populations have been marginalized; feelings of frustration appear, in particular because of the mediatic impact of the discoveries from which they are often excluded. But, these local populations are the guardians of the heritage. Things are changing gradually and today, more and more field researchers get involved with the local needs. Our commitment of scientist as responsible citizen is fundamental: education is a right for all as expressed in the universal declaration of human rights. During the expeditions of our team to Africa, fossil apes and hominids were discovered in three African countries on which this article is focused: Uganda, Kenya and Namibia. These data suggest that the evolution of the apes did not take place exclusively in Eastern Africa, but was more panafrican, a proposal later confirmed by finds in Central and Western Africa. These discoveries were made with citizens of each of these countries and one way of getting feedback to the local people is to train young scholars in our field as well as to build local museums or exhibits, for educational purposes. For many years, knowledge was transferred outside the African continent, but today as before it is the right of the people and the duty of the scientists to leave it locally. There is an appropriation by the people of their heritage, which is an advantage for its preservation and the future of education. In some cases, field museums became tourist attractions; in the long term, the scientific culture could be part of sustainable development.